Nutrient Cycling and Plant Nutrition in Forest Ecosystems - Xiangyang Sun (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Nutrient cycling is essential for maintaining nutrient supply to forest plants and for enhancing forest productivity. Nutrient cycling is also strongly linked to greenhouse gas emissions and thus to global climate change. Nutrient cycling and plant nutrition can be severely affected by anthropogenic and natural disturbance regimes. This Special Issue will provide an avenue to publish recent progress on research on nutrient cycling and plant nutrition in forest ecosystems and how nutrient cycling and plant nutrition are affected by disturbance regimes such as harvesting, atmospheric deposition and climate change.